Análise citogenética em algumas espécies de peixes em uma região de divisor de águas entre riachos de bacias hidrográficas distintas - Ferreira Neto, Maressa (Universidade Federal de São Carlos, 2008)
Cytogenetics studies in headwaters fishes have contributed significantly to the citotaxonomy and cytossistematic of these organisms. However, little is known about this diversity in the vast majority of river basins, especially among populations of adjacent basin headwaters, as it occurs in the Corumbataí area of environmental protection (Área de Proteção Ambiental APA Corumbataí), São Carlos city, São Paulo state. This way, an attempt was made to perform a comparative karyotypic analysis among the populations of many fishes of the Feijão upstream, tributary of Jacaré-Guaçu river, Tietê basin, and the Pântano upstream, tributary of Mogi-Guaçu basin, associating the cytogenetic data with the evolutionary aspects and the dispersal of the species in the region. Were studied species belongs of five Pisces families: Characidae (Astyanax altiparanae, Astyanax fasciatus, Moenkhausia sanctafilomenae); Curimatidae (Cyphocharax modestus); Prochilodontidae (Prochilodus lineatus); Cichlidae (Geophagus brasiliensis, Cichlasoma facetum); and, Gymnotidae (Gymnotus carapo, Eigenmannia sp.). The Geophagus brasiliensis, Gymnotus carapo and, Astyanax altiparanae species were characterized using basic and molecular cytogenetics tools aiming to verify the similarities and/or the chromosomal changes occurred between allopatric species, while in the others were observed inherent specific problems only in one population. A great similarity of the karyotypic macrostructure was observed between G. brasiliensis and Gymnotus carapo populations in both regions studied. However, in A. altiparanae specie differences were detected in the karyotypic formulae and in the number of 18S ribosomal sites. So, the data obtained to G. brasiliensis and G. carapo indicate that despite they are separated by waters divisors, occurred the maintenance of a very similar karyotypic macrostructure, possibly reflecting a karyotypic stability of this specie. However, in A. altiparanae specie we can observe a certain degree of evolutionary divergence between the analyzed populations, resulted of a flow gene restriction.
Keywords: Citogenética de peixes; Cromossomos B; Citogenética - peixes neotropicais; Polimorfismo; CIENCIAS BIOLOGICAS::ECOLOGIA